A critical evaluation and analysis of methods of determining the number of times that lightning will strike a structure - Ngqungqa, Sphiwe Hamilton (My University, 2006)
The primary objective of this paper is to present results regarding data obtained from Eskom’s Lightning Positioning and Tracking System (LPATS) and is a continuation of the work presented at the two SAUPEC Conferences in Pretoria and Stellenbosch [1, 2]. LPATS provides some useful information regarding the lightning field measurements around the Brixton and Hillbrow Towers, in Johannesburg, for the two seasons of June 2001 to June 2003. The results suggest that there is a significant increase in apparent ground flash density in the vicinity of the towers when compared to the surrounding areas. The observation of mean current values in the order of -20kA suggests that the increased contribution of upward flashes to the total incidence of flashes in tall structures should lead to a decrease in measured current amplitudes.
Faculty of Engineering & Built Environment, School of Electrical & Info Engineering, Dissertation
Keywords: Tall structures; current amplitude; critical height